Parenting Children with Disorders of Sex Development (DSD): A Developmental Perspective Beyond Gender - Wisniewski, A. B.; Sandberg, D. E. (Hormone and Metabolic Research, 2015)
Advances in therapeutics for specific conditions have contributed to a categorical psychological approach to chronic diseases that affect children. Consensus statements and clinical guidelines recognize stress associated with disorders of sex development (DSD) for patients and their caregivers – yet much remains to be learned concerning the social adjustment, mental health, and quality of life of affected children and their families. We present preliminary data on the psychosocial comorbidities of caregivers of children with DSD, including stigma, isolation, stress, anxiety, and depressive symptomatology. Evidence is offered in support of individualized psychological approaches for families according to such variables as: 1) gender of the caregiver, 2) gender of the affected child and 3) presence of genital ambiguity at birth. Development of feasible, targeted interventions to ameliorate psychosocial comorbidities among caregivers is needed to optimize social adjustment, mental health, and health-related quality of life (HRQoL) for children with DSD.
Keywords: disorders of sex development; congenital adrenal hyperplasia; androgen insensitivity syndrome; psychosocial; chronic illness; parents